TRANSFORMATION OF STATE LOGISTICS POLICY IN THE CONDITIONS OF SOCIO-ECONOMIC CHALLENGES - GUPALO, Volodymyr; SAMOILENKO, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to substantiate the theoretical and methodological principles and determine the directions of transformation of the state logistics policy in the conditions of modern socio-economic challenges, as well as to determine the directions for improving the mechanisms of state regulation of logistics processes. The article examines the theoretical and methodological principles and the practical aspects of transforming state logistics policy in the context of modern socio-economic challenges. The essence of state logistics policy is a complex of regulatory, institutional, infrastructural, and financial measures aimed at ensuring the effective functioning of the transport and logistics system, increasing the competitiveness of the economy, and stimulating socio-economic development. The role of logistics as a strategic tool for modernizing economic systems, which reduces transaction costs, accelerates capital turnover, and integrates national producers into global supply chains, is substantiated. The approaches to state regulation of the logistics sector are analyzed, and the advantages and limitations of direct and indirect mechanisms of influence are determined. Special attention is paid to the problems of developing transport and logistics infrastructure, digitalization of flow process management, greening of transportation, and the formation of adaptive strategies for state logistics policy. Based on the generalization of domestic and foreign experience, directions for improving state management in the field of logistics are determined: modernization of transport and logistics networks, introduction of innovative digital technologies, development of public-private partnership, harmonization of the regulatory framework with international standards, and stimulation of “green” logistics. It is substantiated that the comprehensive implementation of these directions provides a synergistic effect of socio-economic activation, contributes to the diversification of regional economies, increases the investment attractiveness of territories, and strengthens integration ties in the global economic space.
Keywords: logistics; state regulation; state logistics policy; logistics infrastructure; international logistics